Efeito da intensidade de desbaste nas características dendrométricas e tecnológicas da madeira de Eucalyptus grandis Hill ex Maiden - Trevisan, Rômulo (2006)
This study was understaken to evaluate the effect of different thinning intensities in the dendrometric and technological characteristics of the wood of Eucalyptus grandis at 14 years of age. There was analyzed a thinning experiment, located in the northern coast of Rio Grande do Sul installed in randomized blocks, with four treatments (T1 = 1638 trees/ha; T2 = 1150 trees/ha; T4 = 589 trees/ha e T8 = 192 trees/ha) and four repetitions. The trees were selected on the basis of the dominant and average diameter of each treatment. After cutting down, the trees were measured and the volume determined by the method of Smalian. Afterwards, disks were taken at the base, 25, 50, 75 and 100% of the commercial height, and at the DBH (Diameter at Breast Height), for basic density and radial shrinkage determination. There were selected the logs located between the DBH and 25% positions, destined to the sawn wood quality evaluations after headrig breakdown, air seasoning and kiln dry. In relation to the dendrometric characteristics, the results indicate that the application of more severe thinnings caused significant gain in diameter at breast height, height and volume in average trees, not influencing the dominant ones. The volume per hectare, on the other hand, diminished gradually with the intensity of the intervention, causing losses of up to 59,6%. In relation to the technological characteristics, the results indicate that the basic density of the average trees was influenced by the thinning, however, without presenting clear trend in relation to the intensity of the intervention. The production of dry mass of the average trees increased with the thinning intensity and did not affect the production of the dominant trees. The radial shrinkage of the dominant and average trees grew in the direction pith to bark, not being modified by thinning intensity. Larger vital space reduced the percentage of end splits of the boards in the dominant trees and did not present a clear trend for the average trees. The processing condition only increased the development of this defect in the dominant trees. The thinning intensity did not ffect the board bow of the dominant trees; however, for the average trees, larger vital space reduced this defect. The processing condition, both for dominant and average trees diminished the magnitude of the bow. Board spring was influenced by thinning in both dominant and average trees; however, without presenting a trend with its intensity. The processing condition did not modify this defect in the dominant and average trees. Knots presented a trend to increase diminishing the intensity of thinning only in the average trees. The results allow to conclude that the quality of the wood depends on the planning and of the applied interventions in the forest